The permanence of the epidemic: Cynicism and mold ontology -Love in the Time of Choleraby Gabriel Garcia Marquez is a model (مجلة إحالات, 2026)
This study seeks to define the cholera epidemic that was adopted by the novelist Gabriel García Márquez's blog - Love in the Time of Cholera - and to trace its symptoms related to the cynic philosophy, aswell as insight into the exacerbation of the soft erotic side and the viscosity and rottenness of all the novelistic construction, and to feel the gloomy character that results from the anxiety of the implicit death in Character souls.From there, the subject monitors the bodies ill with love disease and their pathological symptoms suchas vomiting and diarrhea that are completely identical to the stoic bacteria, in addition to paying attention to the vital role employed by the water formula in the novel and following these waterways to stand up to the permanence and infinity of the epidemic. The study also exposes a group of deep-rooted authoritarian centralities in the fictional text, to show the placeof compatibility between them and the cholera pandemic.